The precarity of gender, migration, and locations: case studies from Bangladesh and Nepal. Issue 2 (17th February 2023) - Wu, Joyce; Kilby, Patrick
ABSTRACT : While migration debates point to both empowerment and disempowerment in the range of choices that women can experience due to patriarchal norms in the home country and families, migration norms themselves can at the same time be disempowering. This paper explores the idea of precarity as a way through this paradox. By using Key Informant Interviews in case studies from Nepal and Bangladesh, we show how the precarity of migration can change not only due to patriarchal norms at the origin and host country but also events such as COVID-19 can have a profound effect on women's choices and agency.